A Journal of Three Months' Walk in Persia in 1884 by Captain John Compton Pyne : Introduction, Notes and Translation - Afsharian, Marjan; Harris, Russell (Book collections on Project MUSE., 2017)
A primary source on a journey to Persia by Captain John Compton Pyne in 1884 revealing the West's fascination with the Middle East in Victorian times. The book includes an introduction by the editors and a transcription of the manuscript with notes and the original illustrations, mainly watercolours. An important historical document and eye-witness account pertaining to Iran, anthropology, area studies, study of 'orientalism' and colonialism, and for historians.